2007
DOI: 10.1016/s0377-1237(07)80055-4
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Food Poisoning in a Military Establishment

Abstract: The chicken dish was the epidemiologically incriminating food item responsible for the outbreak. Clinical and epidemiological features were suggestive of salmonella food poisoning. However, same could not be confirmed bacteriologically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…6 The mode of transmission also may not be evident in many situations. 7 In a study, conducted in New Zealand between 2000 and 2009, 204 outbreaks of non-typhoidal salmonellosis were analyzed. The results showed that nontyphoidal salmonellosis was primarily a food borne disease in New Zealand, but there was insufficient evidence to confirm important food vehicle.…”
Section: Discussionmentioning
confidence: 99%
“…6 The mode of transmission also may not be evident in many situations. 7 In a study, conducted in New Zealand between 2000 and 2009, 204 outbreaks of non-typhoidal salmonellosis were analyzed. The results showed that nontyphoidal salmonellosis was primarily a food borne disease in New Zealand, but there was insufficient evidence to confirm important food vehicle.…”
Section: Discussionmentioning
confidence: 99%
“…Mostly, army and military establishments have their own food procurement systems which are dedicated to the prevention of both unintentional and intentional contamination of food. Nevertheless, foods consumed at military institutions have been also identified as an important source of food-borne outbreaks (9), including outbreaks caused by viruses, such as Norovirus or Hepatitis A (10)(11)(12)(13), bacteria, such as Salmonella spp., Staphylococcus aureus (14)(15)(16)(17), but also toxins such as histamine (18) or scromboine (19) associated with eating yellow fin tuna (Thunnus albacares). Despite the fact that military staff usually includes health people in good physical condition, they still constitute a high risk group for food poisoning due to the community kitchen practice and common meals (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Several gastroenteritis outbreaks have been reported in India after chicken containing food consumption. 7, 8 A study conducted by synthesizing evidence from 10 outbreaks in Hyderabad observed more outbreaks in marriage functions and at the household level, with chicken biriyani as one of the main food item implicated and the etiological agent in most of the cases was S. aureus and in one case Salmonella species was isolated. 9 Based on the clinical features of the case patients with loose stools and abdominal pain as the primary symptom without vomiting suggest infection with Bacillus cereus or Clostridium perfringens , both having an incubation period ranging from 6 to 18 hours responsible for the outbreak.…”
Section: Discussionmentioning
confidence: 99%